Study on the feasibility of the micromix combustion principle in low NOx H2 burners for domestic and industrial boilers: A numerical approach. (1st December 2021) - Lopez-Ruiz, G.; Alava, I.; Blanco, J.M.
Abstract: The purpose of the present investigation is to explore the feasibility of applying the micromix combustion principle (MCP) to design low NO x burners using 100% H2 as fuel for domestic and industrial boilers. Previous investigations studying the MCP on stationary and aero gas turbine applications, showed low NO x emissions without flashback risk, which represent the two main issues when burning 100% H2 . Since boiler burner operating conditions differ from gas turbine combustors, the present paper studies the MCP through CFD calculations under re-defined conditions for domestic and industrial burners, adapting the energy densities, air-fuel equivalence ratios and pre-heated air temperatures. A reference geometry was built to validate the selected numerical models with experimental results from literature. Afterwards, burners were re-dimensioned following an existing geometry-scaling methodology. The obtained results evidenced that MCP characteristics were still maintained for the defined cases, keeping low NO x values between 4 and 14 ppm. The numerical results were also validated through experimental NO x measurements in a laboratory scale micromix burner prototype. In order to assess the benefits of using hydrogen micromix burners in domestic and industrial boilers, the present work includes a final discussion with practical design considerations. The present study lays the groundwork for complementary experimental research work, which is being carried out in laboratory-scale prototypes. Highlights: MCP is a potential technology for domestic and industrial hydrogen burners. Low NO x and MCP characteristics are preserved for the defined cases. The lower entropy production in H2 combustion allows working with higher AFR. Higher AFR could be beneficial for domestic and industrial low NO x H2 burners.